CRIMINAL LIABILITY FOR FINANCIAL FRAUD CRIMES - Nadhim Jawad Al-Maamouri (International Journal of Business, Law and Political Science, 2026)
Objective: The objective of this study is to determine the optimal level of customer service quality, as measured by the customer satisfaction index. The primary focus of this study is to ascertain the extent to which the protection of intellectual property rights for individuals and institutions is guaranteed, and to establish the general principles that govern the relationship between the public and the government in the context of intellectual property rights. Method: The present study is an evaluation of the comparative study between the Iraqi legislation and a number of other Arab legislation (including the Egyptian legislation). Results: The study revealed a discrepancy in the policy evaluation process. Specifically, it was observed that the legislative approach adopted in the evaluation was not consistent with the prevailing legal standards, which are characterised by a more stringent approach. Novelty: It is imperative that the legislative vacuum concerning contemporary crimes is addr the introductionessed, and that the criminal justice system is strengthened by establishing clear penalties for new crimes and by ensuring that the law is applied equally and fairly.